Symmetrical double‐loop H‐field probe with floating shield for improving sensitivity and electric field suppression - Jiesheng Liu; Meizhen Xiao; Xiao He; Wenxiao Fang; Weiheng Shao; Quan Huang; Guoguang Lu; Lei Wang; Yun Huang; Yunfei En; Ruohe Yao (IET Microwaves, Antennas & Propagation, 2021)
Abstract A magnetic near‐field probe (H‐field probe) with dual output has been developed using a four‐layer printed circuit board (PCB) technique. To achieve the improvement of detection sensitivity, the symmetrical double‐loop is adopted to double the detection signal while suppressing the electric field coupling, which is also illustrated in a circuit model. The calibration factor (defined as the ratio of the external magnetic field to the induced response voltage of the probe) of the proposed H‐field probe reaches 37.74 [dB (A/m)/V] at 0.5 GHz with the loop area of 0.8 mm2, resulting in a better sensitivity than the single‐loop probe. For the suppression of unwanted electric field a floating shield is added to the bottom of the probe, leading to an excellent common electric field suppression ratio of 29 dB in the frequency range up to 10 GHz. The probe is also characterised by parameters such as high differential electric field suppression, spatial resolution and probe influence on the device under test.